Prognostic value of cetuximab‐related skin toxicity in metastatic colorectal cancer patients and its correlation with parameters of the epidermal growth factor receptor signal transduction pathway: Results from a randomized trial of the GERMAN AIO CRC Study Group. Issue 1 (26th June 2012) - Stintzing, Sebastian; Kapaun, Christine; Laubender, Rüdiger Paul; Jung, Andreas; Neumann, Jens; Modest, Dominik Paul; Giessen, Clemens; Moosmann, Nicolas; Wollenberg, Andreas; Kirchner, Thomas; Heinemann, Volker
Abstract Skin toxicity is a frequent adverse event of epidermal growth factor receptor (EGFR) targeting agents. Occurrence of cetuximab‐induced skin toxicity (Cet‐ST) correlates with better treatment response and longer survival times. Molecular markers predicting Cet‐ST are still missing. This investigation analyzed the value of Cet‐ST for treatment efficacy in a randomized trial comparing cetuximab plus capecitabine/irinotecan to cetuximab plus capecitabine/oxaliplatin as first‐line treatment of metastatic colorectal cancer. Patient characteristics and molecular parameters (KRAS mutation, EGFR‐FISH, EGFR‐IHC and EGFR intron‐1 polymorphism) of the tumour were correlated with response and Cet‐ST. Cet‐ST grade 0–1 was observed in 31%, grade 2–3 in 69% of patients. Outcome favoured patients with grade 2–3 Cet‐ST with regard to overall response rate (62 vs. 41%), PFS (7.8 vs. 5.2 months) and overall survival (OS) (30.3 vs. 18.0 months). First‐cycle rash was observed in 66% of patients and corresponded with longer survival (30.7 vs. 20.2 months, p = 0.007). Patients without Cet‐ST had a poor outcome (PFS, 1.9 months; OS, 11 months). The correlation of Cet‐ST with survival was specifically evident in patients with KRAS codon‐12‐mutated tumours assumed to be cetuximab resistant. In multivariate analysis of patient characteristics, male gender and younger age were significantly correlated with Cet‐ST. Among molecular parameters, no significant correlation with Cet‐ST was found. Cet‐ST is an early predictor of treatment efficacy in cetuximab‐treated patients. This effect of Cet‐ST is independent of the KRAS mutation status, suggesting that Cet‐ST rather relates to constitutional factors of the patient than alterations of the EGFR pathway in the tumour.